Compression garments for recovery from muscle damage: evidence and implications of dose responses - Brown, F. C.; Hill, J. A.; Pedlar, C. R. (Current Sports Medicine Reports, 2022)
The use of compression garments (CG) has been associated with improved recovery following exercise-induced muscle damage. The mechanisms responsible are not well established, and no consensus exists regarding the effects of compression pressure (i.e., the "dose"), which until recently was seldom reported. With the increasing prevalence of studies reporting directly measured pressures, the present review aims to consolidate current evidence on optimal pressures for recovery from exercise-induced muscle damage. In addition, recent findings suggesting that custom-fitted garments provide greater precision and experimental control are discussed. Finally, biochemical data from human trials are presented to support a theoretical mechanism by which CG enhance recovery, with recommendations for future research. The effects of compression on adaptation remain unexplored. More studies are required to investigate the relationship between compression pressure and the recovery of performance and physiological outcomes. Furthermore, improved mechanistic understanding may help elucidate the optimal conditions by which CG enhance recovery.